(untitled) (PRÁXIS EM SAÚDE, 2026)
The present study presents an experience report on the late diagnosis of autism spectrum disorder (ASD) in a 20-year-old young woman. The narrative seeks to explore, in a reflective and personal manner, the challenges faced throughout life without a formal diagnosis, the impacts of this absence on identity formation, relationships, and mental health, as well as the transformations that emerged after the recognition of autism. The methodology is grounded in autobiographical writing as a tool for reclaiming, analyzing, and re-signifying lived experiences. Supported by specialized literature on late diagnosis in autistic women, the report aims to articulate subjective and academic elements that highlight the importance of early recognition and qualified listening in the trajectories of autistic individuals. It concludes that the diagnosis, even when late, enables a profound process of self-understanding, emotional validation, and restructuring of daily life, promoting greater autonomy and social belonging.